Scale development on educational value of the history of science - Laçin Şimşek, Canan; Çalışkan, Hüseyin (Journal of Turkish Science Education, 2016)
This study was aimed at developing a scale for revealing the views of teachers concerning the educational value of the history of science. To this end, the draft scale form, which was composed of 37 items, was administered to primary school teachers, science and technology, mathematics and social science teachers, working in elementary and middle schools in various Turkish cities. While the exploratory factor analysis was conducted with 350 teachers, the confirmatory factor analysis was carried out with 161 teachers. A three-factor model, entitled “Understanding and Being Interested in Science”, Understanding the Scientific Process” and “Outlook on Science and Scientists”, explaining 56.94% of the total variance, was obtained through the exploratory factor analysis. The first-order and the second-order confirmatory factor analyses demonstrated that the three-factor model of the scale had a theoretical and statistical fitness.